Volunteering in Lithuania: Comparative, Dynamic and Value Perspective - Savicka, Aida (Socialinė teorija, empirija, politika ir praktika, 2021)
Although volunteering is not a new topic in social research, many questions about people’s motivation to engage in voluntary activities still remain open. The article analyzes the changing attitudes towards volunteering in contemporary society, the demographic profile of volunteers, their intrinsic motivation and the cultural value orientation that supports it. The main purpose of this article is to identify the impact of main sociodemographic and personal characteristics in people’s decision to volunteer. Data from European Values Surveys (1990, 1999, 2008, 2017) are used for this purpose.The presented research data provide valuable insights into long-term trends in the development of volunteering in Lithuania, important socio-demographic determinants of volunteering and changing individual motivation to engage in volunteering. As the analysis reveales, although demographic factors – gender, age, education, occupational employment – are important, they only become meaningful when analyzed along with personal characteristics of respondents (such as life satisfaction, trust in people, belief that one is in control of own life) and their value orientations (such as caring, creativity, stimulation, and the pursuit of social justice). In other words, volunteers cannot be treated as a demographically homogeneous group. This means that in order to effectively mobilize people for a specific volunteering activity, it is necessary to take into account not only which socio-demographic groups are generally more likely to be involved, but also the values that are most important to them when planning volunteering strategies and communication. Understanding the determinants of volunteering can serve as a guideline for the development of volunteer-friendly public policies and for properly motivating people to become involved in volunteering, both at the level of the state and specific public organizations.
Keywords: volunteering; volunteering styles; value orientation; individualization; personality